The Role of Pesticide Exposure and Chronic Physical Exertion in Rheumatoid Arthritis Development - Mechanisms and Clinical Implications - A Narrative Review - Zięba, Natalia; Czech, Mateusz; Tarczyński, Dominik; Mazur, Anna; Ciesielska, Dominika; Czmok, Jakub; Kociuba, Katarzyna; Chojęta, Michał; Brzusek, Mikołaj; Cisłak, Miłosz (Quality in Sport, 2026)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease influenced by both genetic and environmental factors. Increasing evidence suggests that exposure to pesticides and excessive physical activity resulting in physiological overload may influence the risk of developing RA. Aim: To summarize current knowledge on the impact of pesticide exposure and physical activity on the risk of developing RA. Material and methods: A narrative literature review was conducted using publications from PubMed and Google Scholar, supplemented with studies from major scientific publishers and medical databases. Epidemiological studies, systematic reviews, meta-analyses, and selected experimental studies on RA risk factors were analyzed. Results: Exposure to pesticides, including insecticides, herbicides, and fungicides, as well as other occupational hazards such as organic solvents, silica, asbestos, animal dust, and engine exhaust emissions, was associated with an increased risk of RA. In contrast, studies on per- and polyfluoroalkyl substances (PFAS) suggested a possible protective effect in women. Regular moderate physical activity was linked to a reduced risk of RA development. Conclusions: Environmental and occupational exposures may contribute to RA development, whereas moderate physical activity may have a protective effect. Further research is needed to clarify these relationships and support effective prevention strategies.